2022
DOI: 10.1155/2022/4641600
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Value of Cytokine Assay in Diagnosis and Severity Assessment of Lung Cancer

Abstract: Purpose. To investigate the clinical value of interleukin 2 (IL-2), interleukin 4 (IL-4), interleukin 6 (IL-6), interleukin 10 (IL-10), tumor necrosis factor α (TNF-α), and interferon-γ (IFN-γ) in diagnosis and severity assessment of lung cancer. Methods. In this observational study, 50 physical examination healthy subjects were included in the control group and 100 lung cancer patients were included in the study group. In the study group, 53 cases with pleural effusion were subgrouped to the pleural effusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Out of all the articles included in the meta-analysis [ 27 – 31 , 45 66 ], only one study [ 27 ] reported a significantly lower level of IL-6, while 20 studies [ 28 , 29 , 39 , 45 52 , 54 , 55 , 58 62 , 65 , 66 ] found a higher level of IL-6 in LC cases than in HCs. The remaining studies [ 30 , 31 , 53 , 56 , 57 , 64 ] did not find any significant difference between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Out of all the articles included in the meta-analysis [ 27 – 31 , 45 66 ], only one study [ 27 ] reported a significantly lower level of IL-6, while 20 studies [ 28 , 29 , 39 , 45 52 , 54 , 55 , 58 62 , 65 , 66 ] found a higher level of IL-6 in LC cases than in HCs. The remaining studies [ 30 , 31 , 53 , 56 , 57 , 64 ] did not find any significant difference between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Other interleukins, such as IL-17, promote angiogenesis and cell proliferation and inhibit apoptosis, correlating with tumor progression. Finally, IL-23 hampers the activity of B, T, and natural killer cells, promoting lung cancer progression and metastasis [ 18 ]. However, the latter two were not measured in patients’ BALF in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, IL-2 is a cytokine secreted by T cells in response to antigen stimulation and is crucial for T cell proliferation and NK cell activity. Other interleukins may promote tumor growth by inhibiting effector T-cell function and enhancing regulatory T-cell function [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, IL-2 is a cytokine secreted by T cells in response to antigen stimulation and is crucial for T cell proliferation and NK cell activity. Other interleukins may promote tumor growth by inhibiting effector T-cell function and enhancing regulatory T-cell function [ 12 ].…”
Section: Introductionmentioning
confidence: 99%